2010
DOI: 10.1203/00006450-201011001-00282
|View full text |Cite
|
Sign up to set email alerts
|

282 Varying Predictive Values Dictate the Need to Standarise Commerical Kits for Ttg Testing

Abstract: In Sweden, a precipitous rise in the incidence of celiac disease (CD) in children below two years of age occurred during 1985-1995 in Sweden. The period is well suited for investigating the socioeconomic and geographical distribution of CD in Sweden. Previous research on the importance of socioeconomic position (SEP) in CD has produced conflicting results. All singleton children born in Sweden 1987Sweden -1993 were identified in the Swedish Medical Birth Record. We linked several other national registries to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 0 publications
3
28
1
Order By: Relevance
“…Environmental influences such as perinatal injury and maternal infection could play a significant role in the context of a susceptible genetic background and contribute to the development of ASD. For instance, premature infants with isolated cerebellar hemorrhage have a 30 fold higher incidence of ASDs compared to the general population (15, 16). Other epidemiological studies have implicated activation of the maternal immune system during gestation as a contributor to the development of various neuropsychiatric disorders (1719) and more specifically in the development of autism (1921).…”
Section: Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental influences such as perinatal injury and maternal infection could play a significant role in the context of a susceptible genetic background and contribute to the development of ASD. For instance, premature infants with isolated cerebellar hemorrhage have a 30 fold higher incidence of ASDs compared to the general population (15, 16). Other epidemiological studies have implicated activation of the maternal immune system during gestation as a contributor to the development of various neuropsychiatric disorders (1719) and more specifically in the development of autism (1921).…”
Section: Genesmentioning
confidence: 99%
“…Second, imaging studies of patients diagnosed with ASD indicate gray and white matter abnormalities in the cerebellum, dating to early childhood (8690). Premature infants with isolated cerebellar hemorrhage have a higher incidence of ASDs, suggesting that cerebellar dysfunction early in life contributes to the pathogenesis of autism (15, 16). The developmental vulnerability of this circuit is further illustrated by study of genetic syndromes associated with ASD.…”
Section: Brain Regions and Neural Circuitsmentioning
confidence: 99%
“…The present study examined the structural characteristics of the three major pathways of the cerebellar peduncles in a healthy pediatric sample. Examining structural properties of the peduncles in children has important theoretical implications for understanding the pathways of neural signals in motor, cognitive, and emotional processes (19, 20). Quantifying individual differences in healthy and typically developing children is a necessary prerequisite to understanding variations in clinical conditions that affect the cerebellum.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, cerebellar volume has not been found to predict outcome at 2 years of age [106], but data are controversial [108]. More recent studies have demonstrated relationships between cerebellar structure and supratentorial development injury [109,110]. …”
Section: Specific White Matter Tract Abnormalitiesmentioning
confidence: 99%